IMPLEMENTASI PENDIDIKAN AGAMA DI DAERAH PASCA KONFLIK {Studi Kasus di Kota Ternate Maluku Utara) - Badruzzaman Badruzzaman (Al-Qalam, 2008)
This research aims to describe the implication of social-religious conflictto education of religion (formal and informal) implementation. Thiswas conducted at Ternate, North Maluku. Data was collected by depthinterview and observation.This research indicates that social-religious conflict was occured at1999 fisically has no impact to educational process. But, this conflicthad give impact to learning process of religion education. Especially,to Christ and Katolik schools. These schools became refugee camp.Nevertheless, local government regulation to education of religion implementationhave been increase after conflict. But, that regulation seemsdo to certain school.